Histochemical Observations of Vagina in Pre-laying and Laying Japanese Quail (Coturnix coturnix japonica) - P. N. Thakur (Indian Journal of Veterinary Anatomy, 2022)
The entire oviduct starting from infundibulum to vagina excised from 12 birds each at 4 week, 5 week th th (Pre-laying period), 6 week and 7 week (laying period) were collected and histochemical observations were recorded on the vagina at different age groups of the pre-laying and laying stages. Histologically, in all age groups of birds, the vaginal wall was composed of three layers viz., tunica mucosa, tunica muscularis, and tunica serosa from interior to exterior. The presence of the glycogen varied from moderate to intense at different ages in various components of vagina suggests the energy source required for development, cellular proliferation, and significant cellular physiological functioning during growth. The weak to moderate ABPAS activity in the lining epithelium and other components of vagina in all ages during the present study may be attributed to its necessity for providing optimum condition for growth and physiological requirements of tissue components.